Bentuk Reduplikasi Bahasa TAA - M. Asri. B, S.Pd., M.Pd. (Balai Bahasa Sulawesi Tengah, 2018)
The focusing of this research was reduplication form of TaaLanguage at AmpanaTeteSub District of TojoUnauna District of Central Sulawesi. This research was purposed to answer the problem of the reduplication form of Taa Language. The method which used in this research was descriptive qualitative method. It was a research method by describing the object of the research as it was, especially which directly related to data collection, data processing, and reporting arrangement of data result. The method which was used including to field research because the research direct to observe, to hear, and to note the recording of reduplication form of Taa Language. The result finding related to reduplication form which was found (a) full reduplication which divided on: full reduplication of nominal class, full reduplication of verbal class, full reduplication of adjective class, full reduplication of adverb class (b) partly reduplication which divided on: partly reduplication of nominal class, partly reduplication of verbal class, partlyreduplication of adjective class, partly reduplication of adverb class (c) combination reduplication by processing affixes form which divided on: reduplication of nominal affixes, reduplication of verbalaffixes, reduplication of adjectiveaffixes, reduplication of adverbaffixes.